INTERNALISASI NILAI-NILAI ASWAJA MELALUI PENGAJIAN KITAB AL-MUQTATHAFAT DI ORGANISASI PAC IPNU-IPPNU DUDUK SAMPEYAN GRESIK - Maftuh Maftuh; Rofiqoh Rofiqoh (JP : JURNAL PENDIDIKAN, 2022)
Abstract: A great nation is discernible in the quality or character of the nation (man) itself. Character building is something of temporal and spiritual competence. One of the defining characteristics of future nations is youth. But looking closely at the issues this beloved nation faces on a daily basis, causes concern, where generations of intelligent people lack an awareness of the importance of moral values and civility and essential values in social life. it is very important to breed amaliyah which print muslims that continue to grow in this regard. Faith, obedience to Allah, and glory. Like amaliyah. Amaliyah was done by nahdlatul scholars' citizens who have become a culture in our daily lives. So, through the practice of teaching the book of al-mugtathofat in the ipnu-ippnu organization that became the place of character building on young people who conform to aswaja values. The problem discussed is: 1) how does the ipnu-ippnu pac organization play Sampeyan gresik in imposing aswaja values? 2) how the process of scripture study activities al-muqtathafat in organitation IPNU-IPPNU PAC Duduk Sampeyan Gresik. The study employs a descriptive qualitative approach, with data analysis using data reduction, data presentation and deduction, so that the data obtained will produce naturally descriptive data, as for the data-collecting techniques using observation, interview and documentation and for the validity of the data relating to source, technik and time. Research shows: 1) the implanting of aswaja values Shared by IPNU-IPPNU PAC Duduk Sampeyan gresik is done through activities carried out either religious or public. Using aswaja kmowing and aswaja feeling. 2) the process of scripture muqtathofat in PAC IPNU IPPNU Duduk Sampeyan uses the method of speech and also aims to instill aswaja values to apply to his environment.Keyword: Ahlussunah wal jama’ah, reciting the book (al-Muqtathafat), IPNU-IPPNU